A Simple Test of the Re-Distributive Nature of Price Changes for Wealth Owners in the United States and United Kingdom - Tait, Alan A. (The Review of Economics and Statistics, 1967)
Alan A. Tait, A Simple Test of the Re-Distributive Nature of Price Changes for Wealth Owners in the United States and United Kingdom, The Review of Economics and Statistics, Vol. 49, No. 4 (Nov., 1967), pp. 651-654